Edukasi Pengolahan Ubi Jalar Ungu dalam Upaya Penurunan Kadar Gula Darah pada Penderita Diabetes Mellitus - Rizki Sari Utami Muchtar; Galuh Eka Safitri; Fitri Fitri; Agnes Monika Hartini (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Diabetes mellitus is a metabolic disorder in which the pancreas does not produce enough insulin and is characterized by hyperglycemia. Tests to diagnose diabetes include fasting blood sugar (FBS), random blood sugar (RBS) , blood sugar 2 hours after eating (GD2PP) and glycated hemoglobin (HbA1C). Purple sweet potato is a non-pharmacological therapy that has a high fiber content, low glycemic index carbohydrates. Dietary foods containing antioxidants, including anthocyanins, can protect pancreatic β-cells from glucose-induced oxidative stress. Administration of purple sweet potato extract can protect pancreatic β-cells from the harmful effects of free radicals. Study shows that purple sweet potato have different glucose level according to how the sweet potato being processed which is boiled, steamed, grilled and fried purple sweet potato, namely 3.30%, 4.92%, 7.72%, and 7.36%, respectively. So it can be concluded that the lowest glucose content was obtained from the boiled purple sweet potato sample. Anthocyanins that found in purple sweet potatoes (Ipomoea batatas poiret) contain substances that can control blood sugar levels, thus preventing insulin resistance in people with diabetes mellitus. The purpose of this program for the resident of Kavling Senjulung RT 02 RW 09 is to know about non-pharmacological prevention of diabetes and start applying it to control blood sugar for people with diabetes mellitus. The implementation method was carried out by providing education related to purple sweet potato processing and demonstrating how to process it and perform medical examination including blood pressure and random blood sugar (RBS) .